2013
DOI: 10.1074/jbc.m113.488478
|View full text |Cite
|
Sign up to set email alerts
|

A Disintegrin and Metalloprotease (ADAM) 10 and ADAM17 Are Major Sheddases of T Cell Immunoglobulin and Mucin Domain 3 (Tim-3)

Abstract: Background: Membrane-bound Tim-3 regulates immune responses. Results: Soluble Tim-3 is generated by A disintegrin and metalloprotease (ADAM) 10 and ADAM17. Conclusion: ADAM proteases are involved in Tim-3 processing. Significance: Shedding of Tim-3 influences immune cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 53 publications
3
106
0
Order By: Relevance
“…As previously described by Moller-Hackbarth et al (33), human Tim-3 was shown to be shed from the surfaces of monocytes by the matrix metalloproteinases ADAM10 and ADAM17, in response to the stimuli PMA and ionomycin. Tim-3 is constitutively expressed on monocytes normally and is weakly expressed on T cells, but it is upregulated on T cells in chronic viral infections (13,38).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…As previously described by Moller-Hackbarth et al (33), human Tim-3 was shown to be shed from the surfaces of monocytes by the matrix metalloproteinases ADAM10 and ADAM17, in response to the stimuli PMA and ionomycin. Tim-3 is constitutively expressed on monocytes normally and is weakly expressed on T cells, but it is upregulated on T cells in chronic viral infections (13,38).…”
Section: Resultsmentioning
confidence: 88%
“…The inclusion of the ADAM10 inhibitor resulted in a significant reduction in the levels of sTim-3 produced across all populations (P ϭ 0.0264); however, it did not completely prevent the production of sTim-3. While this could be a dosing issue with the inhibitor, ADAM17 may have contributed to Tim-3 shedding, as previously described (33). However, inhibitors specific for ADAM17 are not currently commercially available.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…BMDMs were detached using Accutase (PAA Laboratories), seeded on 6-well plates at a density of 0.5 ϫ 10 6 cells/ml, and stimulated the next day as indicated. Primary human macrophages were generated as previously described (24). Briefly, peripheral blood mononuclear cells were isolated from human blood by density gradient centrifugation and monocytes were subsequently purified with CD14 MicroBeads according to the manufacturer's instructions (Miltenyi Biotec, Bergisch-Gladbach, Germany).…”
Section: Methodsmentioning
confidence: 99%